2002
DOI: 10.1046/j.1365-2249.2002.01757.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining a T-cell epitope within HSP 65 in recurrent aphthous stomatitis

Abstract: Recurrent aphthous stomatitis (RAS) is the most common disease of the oral mucosa, affecting at least 10% of the general population [1]. The onset of RAS usually presents during adolescence, and the course of the disease is characterized by recurrences followed by remissions. The disease may persist for many years and varies from minor ulcers, which may cause transient discomfort, to major ulcers which are associated with pain, inability to eat and loss of weight [2].The aetiology of RAS has not been determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 30 publications
1
30
0
3
Order By: Relevance
“…This is achieved with its capability to recognize the mali- cious antigens and to prevent their catastrophic action as well as the autodestructive immune response. Given that there is no difference between the foreign body and the autoantigen, some authors suggested that the cells of the immune system react to the antigens only by the presence of cytokines (Hasan et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved with its capability to recognize the mali- cious antigens and to prevent their catastrophic action as well as the autodestructive immune response. Given that there is no difference between the foreign body and the autoantigen, some authors suggested that the cells of the immune system react to the antigens only by the presence of cytokines (Hasan et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity to certain food substances, oral microbes such as Streptococcus sanguis, and microbial heat shock protein have been suggested as possible causative factors, but there is still no conclusive evidence to support allergy as a major cause of RAS 48,49 . Although some studies reported that RAS patients tend to have hypersensitivity to environmental allergens, other reports did not find significant correlation between hypersensitivity and RAS.…”
Section: Allergic Factorsmentioning
confidence: 99%
“…Early work suggested a relationship between several immune-mediated reactions and development of RAS. These include cytotoxicity of T lymphocytes to oral epithelium, antibody-dependent cell-mediated cytotoxicity, and defects in lymphocyte subpopulations 49,54,55 . One theory is that multiple immune reactions cause damage induced by deposition of immune complexes within the oral epithelium.…”
Section: Immunologic Factorsmentioning
confidence: 99%
“…Hypersensitivity to some food components and oral microbial agents are considered potential etiological factors. 1,16,17 The association between RAS and some nutritional and blood deficits has been studied, and patients with RAS have been proved to present iron, B12 vitamin, folic acid and hemoglobin deficits more frequently. 18 The fact that 5-10% of patients with RAS present low blood levels of folate, zinc, iron, and B1, B2, B6 and B12 vitamins may suggest these nutritional deficits as potential causes.…”
Section: Introductionmentioning
confidence: 99%